Whiskers and lies : a magical cats mystery - Kelly, Sofie, 1958- (Kelly, Sofie, 1958- Magical cats mystery, 2023)
"Librarian Kathleen Paulson is always willing to help a friend, but to save one from a wrongful arrest, she will need magical backup from her affectionate cats in the newest installment of this New York Times bestselling series. Baker Georgia Tepper has been hired to provide delicious and spooky cupcakes for the Reading Buddies Halloween Party at the library, and she and Kathleen are meeting to finalize the menu of festive confections. Unfortunately, once Georgia's former mother-in-law ambushes her at the library and threatens Georgia with legal action, the afternoon of fun is soured. When Georgia's litigious in-law is later found dead and the friendly baker is implicated, Kathleen is eager to help prove her innocence. Luckily, Kathleen and her intrepid magical cats, Hercules and Owen, have solved their fair share of mysteries. As a result, she knows that in life as well as crime solving, it is all relative, but with hard work, she can make sure the right criminal is booked"--